2014
DOI: 10.1063/1.4857675
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of vortex-wall interaction in low viscosity shear thinning fluids

Abstract: We apply a pseudospectral method to numerically study the dynamics of vortices found within a low viscosity non-Newtonian fluid with a Carreau fluid rheology. The application of a Carreau fluid rheology avoids the commonly observed complications in power-law models at zero strain-rate. We find that fluids with a shear thinning rheology will preserve the small scale features of the flow. In particular, for vortex-solid wall interactions, shear thinning fluids can exhibit behavior associated with Newtonian fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…At lower Reynolds number, drag coefficients show a stronger dependence on Carreau number in shear-thinning fluids. Olsthoorn, Stastna & Steinmoeller (2014) observed that the interaction of the shear layer with the boundary wall yielded higher levels of kinetic energy in a shear-thinning fluid compared with a Newtonian fluid. They also obtained slower decay of enstrophy owing to smaller dissipation in the shear-thinning fluids.…”
Section: Introductionmentioning
confidence: 99%
“…At lower Reynolds number, drag coefficients show a stronger dependence on Carreau number in shear-thinning fluids. Olsthoorn, Stastna & Steinmoeller (2014) observed that the interaction of the shear layer with the boundary wall yielded higher levels of kinetic energy in a shear-thinning fluid compared with a Newtonian fluid. They also obtained slower decay of enstrophy owing to smaller dissipation in the shear-thinning fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Olsthoorn et al [10] studied numerically the vortex dynamics in a non-Newtonian low viscosity fluid following Carreau rheological model. The steadystate mixed convection of Bingham fluids in a cylindrical enclosure with a heated rotating top cover has been numerically analyzed by Turan et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…A shear-thinning fluid typically exhibits viscosity plateaus at both zero-shear-rate (η 0 ) and infinite-shear-rate (η ∞ ). The Carreau-Yasuda model, which captures these plateaus, is thus better suited for characterization of these polymer solutions than the power-law model 2 [11]. Depending on the shear rates, vortex ring can experience two distinctive viscosity variation, (1) power-law variation, and (2) a constant viscosity corresponding to the viscosity plateaus.…”
Section: Introductionmentioning
confidence: 99%